Influence of GFRP Confinement of Reinforced Concrete Columns Exposed to Sodium Chloride on Microstructure and Hydration Products - Husayn, Naseebah; Aljewifi, Hana; Limam, Oualid (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper explores the effect of sodium chloride (NaCl) on microstructure and hydration products of cylindrical column concrete and compares the results after covering it with Glass Fiber Reinforced Polymer (GFRP). 20 short RC columns were prepared with a single concrete mixture. The specimens have cured in different concentration of NaCl (0, 5%, 10%, 15%), some specimens cured directly in solution and other specimens exposed to wet and dry cycle. These specimens were tested, a first group after 28 days of curing, second group after 56 days, while the third group was repaired by GFRP after 28 day then returned to the cured environment and tested after56 day. In order to determine the main crystalline phase composition of concrete specimens and for phase identification of a crystalline material, scanning electron microscopy (SEM) morphology of microstructure concrete and X-ray diffraction (XRD) have been used. The results revealed denser microstructure with the concentration of NaCl crystalline, existence of binding chloride as free halite, chemical pound as a Friedel’s salt or Physical binding held to the surface of hydration products. In addition, the corrosive compounds were observed, and the hydration product phase decreased due to concentration of curing environment. Furthermore, the results from the samples that were covered with GFRP showed that the value of the hydration products didn't change when compared with the samples that were tested after 28 days, moreover, the voids were found in them when compared with the samples exposed to the environment damage without covering it with GFRP.